Teaching Speaking for Professional Context Using Prezi in the Relation With Students’ Creativity - Lina, Marisa Fran (UIN Salatiga, 2018)
This research aims at finding out whether Prezi is effective to teach speaking and the students having high creativity have better speaking skill than those having low creativity. This research was carried out at IAIN Salatiga in the academic year of 2015/2016. The population was the second semester students of English Education Department. In this research, the researcher used experimental research method. The researcher took one class for experimental class (TBI D). This class was divided into two groups (the students having high and low creativity). The research instruments consist of students’ creativity test and a speaking test. The creativity test and speaking test were readable after they were tried out in class TBI D of English Education Department of IAIN Salatiga. The data were the result of speaking test and it was analyzed by multifactor analysis of variance 2 x 2 (ANOVA). The findings of the research show that: (1) Prezi is effective for teaching speaking; (2) The students who have high creativity have better speaking skill than those having low creativity. Based on the research findings, it can be concluded that: Prezi is an effective teaching media to teach speaking and it is suggested to the English Teacher to apply Prezi in teaching speaking. Prezi is suitable for both students who have high and low creativity because it is designed in a variety of formats that helps students to process information and organize their ideas.Key words: Prezi, Teaching Speaking, Creative Students